On Christian Asylum in Augustine’s Sermones - Hrnčiarová, Daniela (Vox Patrum, 2023)
In the late 4th century, bishops utilized the so-called ius intercessionis right to intervene in order to help those in need, be they the persecuted, the accused or the convicted. These actions of a bishop were rooted foremost in the idea of mercy and it was also due to this right that a bishop became the one to decide about the granting of the right to asylum – a right which was gradually extended to Christian churches at the time. St. Augustine encounters the issue of Christian asylum as the bishop of Hippo Regius in Africa mainly in his preserved correspondence, but he talks about seeking sanctuary in Christian churches also in one of his sermons, specifically in Sermo 302 delivered on the feast of St. Lawrence. This paper focuses on presenting the circumstances of a violent act in Hippo Regius and its implications to potentially sanctuary seeking in local Christian church, particularly on the ground of analysis of post sermonem to Sermo 302.